Research on the design and application of “MOOC + flipped classroom” for basketball courses in colleges and universities from the perspective of education modernization - Ti Hu; Hong Liu; Fan Xia (Frontiers in Psychology, 2023)
BackgroundThe wave of education information based on the “Internet+” has swept the world, and the traditional teaching mode can no longer meet the new needs of education teaching, so the teaching mode of “MOOC+ flipped classroom” has attracted widespread attention educators.ObjectiveThis study explores the effect of “MOOC+ flipped classroom” on the teaching design and application of basketball courses in colleges and universities from the perspective of education modernization in order to promote the development of students’ core literacy and provide a more theoretical basis and practical support for the in-depth research and promotion of “MOOC+ flipped classroom” teaching mode.MethodsThis study adopts a quasi-experimental design to study the teaching of basketball courses in colleges and universities based on “MOOC +flipped classroom.” The experimental class adopted “MOOC+ flipped classroom” teaching (34 students), and the control group adopted traditional classroom teaching (30 students). Before and after the 16-week intervention, the student’s learning effects were measured by basketball skill level assessment, Cooperation Ability Scale for University Students, Utrecht Work Engagement Scale-student, and Self-regulated Learning Scale, and the data were analyzed by independent sample t-test and repeated-measures ANOVA.Conclusion(1) Compared with the traditional classroom teaching mode, the “MOOC+ flipped Classroom” teaching mode is innovative in terms of teaching philosophy, teaching resources, and teaching methods, which promotes the change of education informatization and further promotes the realization of education modernization. (2) The “MOOC+ flipped classroom”-based teaching design for basketball courses benefits students’ basketball skill level, study engagement, cooperation ability, and self-regulated learning ability, thus effectively promoting the students’ core literacy.